Media Dan Program Promosi Kesehatan Rumah Sakit Umum Daerah Di Kabupaten Purwakarta - Anisa, Renata; Yustikasari, Yustikasari; Dewi, Retasari (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Media is a tool used by companies or institutions to convey information to the public. The media has an important role in the success of a promotional program. Hospitals have the function of improving public health status by conveying information and health education in accordance with the Minister of Health of the Republic of Indonesia Number 44 of 2018 concerning the implementation of health promotion. This study aims to determine the media and health promotion program at the Regional General Hospital in Purwakarta Regency. The method used is descriptive qualitative with data collection techniques of observation, interviews, and literature study. The results showed that the RSUD in Purwakarta Regency used internal media including audio and visual media, posters, leaflets and banners for health promotion to patients, patient families and hospital human resources. Meanwhile, for health promotion targeting the external public, hospitals utilize digital media such as websites, Instagram, Facebook and YouTube. Health promotion programs implemented by the hospital include education on healthy lifestyles, drug use, dental care, and other health education related to the top ten diseases in hospitals. The hospital periodically evaluates health promotion activities.